Clinical Profile and Allergens in Pigmented Cosmetic Dermatitis and Allergic Contact Dermatitis to Cosmetics in India. Issue 5 (September 2018) - Sharma, Vinod K.; Bhatia, Riti; Yadav, Chander P.
Abstract : Background: Pigmented cosmetic dermatitis (PCD) is frequently encountered in dark-skinned individuals as gradual hyperpigmentation on the face without preceding erythema or itching. Little is known about the allergen profile in PCD. Objectives: The aim of the study was to describe the clinical profile and common allergens in PCD and allergic contact dermatitis (ACD) to cosmetics in Delhi. Methods: Records of patients suspected of PCD and ACD to cosmetics were analyzed. All patients were patch tested with the Indian standard series, Indian cosmetic and fragrance series, and personal cosmetics and, in relevant cases, hairdresser series. Results: One hundred six patients were analyzed. Patch test was positive in 77 cases (72.6%). Cetrimonium, gallate mix, thiomerosal, and skin lightening creams were more frequently positive in cases of PCD ( P = 0.019–0.003), whereas p -phenylenediamine, toluene-2, 5 diamine sulfate, p -aminophenol, m -aminophenol, and nitro- p -phenylenediamine were predominantly positive in ACD to cosmetics ( P < 0.001). Conclusions: Preservatives, antioxidants, and skin lightening creams seem to play a role in causation of PCD, whereas hair dye allergens cause ACD to cosmetics in India.